ChemInform Abstract: Effect of Cation Ordering on the Electronic and Lattice Dynamic Properties of Ag2CdGeS4 Polytypes: First‐Principle Calculation. Issue 23 (16th May 2013) - Wei, Lei; Fan, Weiliu; Li, Yanlu; Zhao, Xian; Yang, Lei
Abstract Theoretical results obtained for three Ag2CdGeS4 polytypes (two of space group Pna21, one of Pmn21) show the effects of cation arrangement on the electronic and lattice dynamic properties such as bonding strength, band structure, and IR spectrum.